Pengaruh Antara Peran Tenaga Kesehatan, Asupan Nutrisi, dan Breast Care Terhadap Kelancaran Pengeluaran ASI pada Ibu Postpartum: The Effect of the Role of Health Workers, Nutritional Intake, and Breast Care on the Smooth Expenditure of Breast Milk in Mothers - Meiliasari, Memey (Dohara POAJ, 2022)
Introduction: Based on the health profile of West Java Province in 2012 as many as 8.7 percent of mothers in Karawang District gave exclusive breastfeeding until their babies were 6 months old. Based on preliminary study data conducted by the researcher in the working area of the UPTD of the Loji Health Center with 10 respondents the results were exclusive breastfeeding reaching 45% per 100 births. Methods: The method used in this study is cross-sectional, which is a sample of 60 respondents. While the analysis technique uses a quantitative approach and analysis using the smartPLS software application approach and Special Package for Statistic Science (SPSS). Results: The results of the study show that there is an influence between research variables. Variables of nutrient intake showed the greatest influence on the smooth expenditure of Asi, with a correlation value of 30.2% compared to other values, the variable influence of the role of health personnel is 16.9% and the effect of breast care is 27.9%. Each variable gives a contribution value and the data variability value is 75.2%. Discussion: variable nutrient intake had the greatest influence against the smooth expenditure of ASI so it's suggested to the head health center and Coordinating Midwife to provide support and counseling about nutritional intake for breastfeeding mothers without food restrictions so that the production of breastmilk obtained is abundant.